Anxiolytic and Antiepileptic Properties of the Aqueous Extract of Cissus quadrangularis (Vitaceae) in Mice Pilocarpine Model of Epilepsy - Moto, Fleur C. O.; Arsa’a, Aren; Ngoupaye, Gwladys T.; Taiwe, Germain S.; Njapdounke, Jacqueline S. K.; Kandeda, Antoine K.; Nkantchoua, Gisele C. N.; Omam Omam, Jean P.; Pale, Simon; Kouemou, Nadege E.; Ayissi Mbomo, Espoir R.; Pahaye, David B.; et al. (Frontiers in Pharmacology, 2018)
Cissus quadrangularis (C. quadrangularis) is a plant of the Vitaceae family known for its anticonvulsant effects in traditional medicine. The objective of this study was to elucidate the anxiolytic and antiepileptic effects of aqueous extract of C. quadrangularis. The mice were divided into different groups and treated for seven consecutive days as follows: a negative control group that received distilled water, po, four test groups that received four doses of the plant (37.22, 93.05, 186.11, and 372.21 mg/kg, po), and a positive control group that received sodium valproate (300 mg/kg, ip). One hour after the first treatment (first day), epilepsy was induced by intraperitoneal administration of a single dose of pilocarpine (360 mg/kg). On the seventh day, the anxiolytic effects of the extract were evaluated in the epileptic mice using the elevated plus maze (EPM) and open field (OP) paradigms. Antioxidant activities and the involvement of gabaergic neurotransmission were determined by measuring the levels of malondialdehyde, reduced glutathione (GSH), GABA, and GABA-transaminase (GABA-T) in the hippocampus of sacrificed epileptic mice. The results show that the extract of C. quadrangularis significantly and dose-dependently increased the latency to clonic and generalized tonic–clonic seizures and decreased the number and duration of seizures. In the EPM, the extract of C. quadrangularis significantly increased the number of entries and the time spent into the open arms and reduced the number of entries and the time spent into the closed arms as well as the number of rearing. The extract of C. quadrangularis also increased the number of crossing, and the time spent in the center of the OP. The level of MDA and the activity of GABA-T were significantly decreased by the extract of C. quadrangularis while reduced GSH and GABA levels were increased. The results suggest that the anticonvulsant activities of C. quadrangularis are accompanied by its anxiolytics effects. These effects may be supported by its antioxidant properties and mediated at least in part by the GABA neurotransmission.